(untitled) (Research, Society and Development, 2024)
Objective: To analyze the narratives of incarcerated puerperal women about the practice of breastfeeding in a prison system in the state of São Paulo, investigating the barriers faced and the impacts on maternal and child health. Method: This is a qualitative, descriptive study, using narrative analysis to explore women’s perceptions. Data collection took place in a penitentiary, where six puerperal women were interviewed, selected according to inclusion criteria such as cognitive preservation and verbal capacity. The interviews, based on a validated questionnaire, were transcribed and analyzed with ATLAS.ti software. Results: The participants reported significant challenges related to breastfeeding, including poor conditions in the prison environment, lack of privacy, early separation from their children and insufficient support from health professionals. Although they had all received a pregnancy card, there were gaps in prenatal care and a lack of guidance on breastfeeding. Most of the puerperae showed feelings of satisfaction in breastfeeding, despite the adversities. The obligatory separation of mother and child after six months was highlighted as a factor of emotional distress. Conclusion: The study highlighted the need for interventions in the prison system to ensure the right to reproductive health and maternal bonding. We recommend the implementation of public policies that promote continuous breastfeeding support, adequate professional training and more humane environments for incarcerated mothers and their children. These advances are fundamental to minimizing negative impacts and promoting maternal and child health in contexts of deprivation of liberty.